Characterization of the high-affinity phosphate transporter PHT1;4 gene promoter of Arabidopsis thaliana in transgenic wheat - E. Peñaloza; M. Santiago; S. Cabrera; G. Muñoz; L. J. Corcuera; H. Silva (Biologia Plantarum, 2017)
The root specificity and phosphate (Pi) deficiency responsiveness of high-affinity phosphate transporter (PHT1) genes point to their promoters as a sustainable system to drive Pi acquisition-related transgenes in plants. In this study, a 3-kb promoter of the AtPHT1;4 gene from Arabidopsis thaliana fused to the β-glucuronidase (GUS) reporter gene was biolistically introduced into wheat (Triticum aestivum L.) and functionally characterized in transgenic plants grown in hydroponics and in pots with soil under various Pi supply rates. From among 27 T1 progeny derived from 250 T0, four transgenic lines reached T3, with two of them showing detectable GUS activity in the roots of T4 plants. An unusually high number of transgene insertions characterized these transgenic lines, along with an irregular pattern of histochemical GUS staining and weak GUS activity. GUS expression driven by AtPHT1;4 was consistently higher under most assay conditions, as it was unaffected by 0 to 0.5 mM Pi in hydroponically grown plants, as well as by 16 to 20 mg(P) kg-1(soil) in potted plants. Raising the soil P up to or above 40 mg kg-1 significantly down-regulated the quantity of GUS transcripts. These results show that the responsiveness of the AtPHT1;4 promoter to Pi availability in transgenic wheat was restricted to soil-grown plants, which highlighted the relevance of the substrate and Pi supply rates in assessing molecular responses to Pi deficiency.